Insulin-Like Growth Factor 1 (IGF- 1) Levels And Left Ventricular Meridional End Systolic Stress (LVMESS) Interrelationship In Middle- Aged And Elderly Obese Subject With Type 2 Diabetes Mellitus - Akeel AMH Zwain; Amina A. Al-Dijaili; Khalid Amber (Kufa Journal for Nursing Sciences)
Background: Left ventricular meridional end systolic stress (LVMESS) is a quantitative determinant index of LV afterload which is an essential determinant of LV performance. The key factors influencing LVMSS, notably ventricular wall thickness, chamber size and configuration are shown to be altered by both obesity and type2 diabetes mellitus (T2DM). There exist reports implicating high free insulin-like growth factor 1 (IGF-1) but not growth hormone (GH) levels, with increased left ventricular mass index (LVMI), abnormal LV geometric remodeling, and A1c levels.